Quality management in entrepreneurship - Murenets, I. (Baltic International Academy, 2018)
У статті автор аналізує управління якістю в підприємництві. Відзначається, що забезпечення якості та контроль якості є двома дуже тісно пов'язаними поняттями, і через їх тісному взаємозв'язку вони часто плутаються і одне неналежним чином використовується в якості заміни іншого. // In the present article, the author analyzes Quality Management in Entrepreneurship. It should be noted, that Quality Assurance and Quality Control are two very closely related concepts and because of that close relationship they are often confused and one is inappropriately used as a substitute for the other.
Keywords: загальне управління якістю; забезпечення якості; контроль якості; total quality management; quality assurance; quality control